A cytochrome P450 from the mustard leaf beetles hydroxylates geraniol, a key step in iridoid biosynthesis. (October 2019) - Fu, Nanxia; Yang, Zhi-Ling; Pauchet, Yannick; Paetz, Christian; Brandt, Wolfgang; Boland, Wilhelm; Burse, Antje
Abstract: Larvae of the leaf beetle Phaedon cochleariae synthesize the iridoid chysomelidial via the mevalonate pathway to repel predators. The normal terpenoid biosynthesis is integrated into the dedicated defensive pathway by the ω-hydroxylation of geraniol to (2 E, 6 E )-2, 6-dimethylocta-2, 6-diene-1, 8-diol (ω–OH–geraniol). Here we identify and characterize the P450 monooxygenase CYP6BH5 as the geraniol hydroxylase using integrated transcriptomics, proteomics and RNA interference (RNAi). In the fat body, 73 cytochrome P450s were identified, and CYP6BH5 was among those that were expressed specifically in fat body. Double stranded RNA mediated knockdown of CYP6BH5 led to a significant reduction of ω-hydroxygeraniol glucoside in the hemolymph and, later, of the chrysomelidial in the defensive secretion. Heterologously expressed CYP6BH5 converted geraniol to ω–OH–geraniol. In addition to geraniol, CYP6BH5 also catalyzes hydroxylation of other monoterpenols, such as nerol and citronellol to the corresponding α, ω-dihydroxy compounds. Graphical abstract: Image 1 Highlights: The cytochrome P450 CYP6BH5 in Phaedon cochleariae was identified as the geraniol hydroxylase. CYP6BH5's role in iridoid biosynthesis was confirmed by using RNA interference. Recombinant CYP6BH5 is a substrate-promiscuous enzyme, that catalyzes the ω-hydroxylation of geraniol, nerol, citronellol but not of linalool. The –OH group of the substrate plays an important role for coordination with the enzyme's catalytic cavity via forming hydrogen bonds.